Draft Genome Sequence of the Chemolithoheterotrophic, Halophilic Methylotroph Methylophaga thiooxydans DMS010 - Boden, Rich (American Society for Microbiology, 2011)
Methylophaga thiooxydans is a mesophilic, obligately halophilic bacterium that is capable of methylotrophic growth on a range of one-carbon compounds as well as chemolithoheterotrophic growth at the expense of thiosulfate. Here we present the draft genome sequence of Methylophaga thiooxydans DMS010 (DSM 22068(T), VKM B2586(T)), the type strain of the species, which has allowed prediction of the genes involved in one-carbon metabolism, nitrogen metabolism, and other aspects of central metabolism.